Artificial Visual System Algorithm applied on Face Recognition and Tracking - Lum, Mi-Fern; Loo Chu, Kiong; Liew Tze, Hui (2008)
The development of an artificial visual system consists of several algorithms based on the biological human eye sight, particularly about the retina. It involves algorithms such as log polar transformation, Gaussian filters, Gabor Wavelets, etc. Overall, the system is implemented into recognition and able to perform some tracking abilities.